Preliminary numerical simulation of steady-state gas-liquid flow in horizontal T-junction - Sam, B. (Asian Research Publishing Network, 2017)
T-junction, or commonly known as stand pipe appendage, is used by oil/gas industries to tap gas from existing production header for the purpose of downstream pipeline instrumentation. The appendage is either pre-design or retro fitted with minimum internals for maximum reliability for remote deployment. The motivation for this research originated from the lack of stand-pipe design method to correctly account for the splitting/separation nature of multiphase fluid within the pipeline straight from the production header. Consequently, a certain amount of liquid migrates together with the gas, resulting in the so-called carryover issue. This situation is further aggravated by the different flow regimes in the header pipeline which is not taken into account by the design practice. The negative consequences of this carryover on the operation of downstream unit have often led to frequent trip and maintenance issues. Therefore, understanding the behavior of gas-liquid flow through T-junction is essence on optimizing the gas phase separation. This study aims to examine the effect of phase volume fraction on the separation of gas-liquid in a T-junction pipe. A computational fluid dynamics (CFD) simulation by means of ANSYS-CFX is employed to model and solve the fundamental mass, momentum and turbulent equations. The computed solutions are compared with experimental data and a satisfactory agreement is achieved. Results show that the gas separation efficiency increases as the initial gas volume fractions increases. © 2006-2017 Asian Research Publishing Network (ARPN).